Analysis of the effect of behavior market segmentation on purchasing decisions of local rice in the modern market. Issue 1 (March 2021) - Lanuhu, N; Rukka, R M; Amrullah, A; Fudjaja, L; Muslimah, C D; Suyono,; Sa'diyah, H
Abstract: The background of this study aims to determine the effect of market segmentation strategies on consumer purchasing decisions in buying local rice, which has traditionally been bought by traditional market communities, but this time is carried out in the modern market. Behavioral variables are very important controlled by the company in order to know what real action they need to remain loyal to the products offered. The variables studied were behavioral variables on purchasing decisions on local rice in the modern market. To find out how much influence the demographic market segmentation variables have on purchasing decisions, this study used a sample of 50 local rice consumer respondents in the Carrefour Pengayoman Makassar Modern Market. While sampling uses a purposive sampling method. The analysis technique used in this research is a descriptive test. Test results show that: Market segmentation does indeed influence the decision to purchase local rice in the modern market.